Supervisi terhadap Kompetensi Perawat dalam Pelaksanaan Keselamatan Pasien Cuci Tangan Five Moment Puskesmas Palmerah - Saharuddin, Saharuddin; Kurniati, Tri; Widakdo, Giri; Widiastuti, Eni; Suadmaji, Suadmaji (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Five moment hand washing patient safety is an action to minimize the risk of services in an effort to prevent and control infection. The aim of this research is to determine the effect of supervision on nurses' competence in implementing five moment hand washing patient safety. uses a Quasi Experiment with a pre post test approach with control group design. The sampling technique used a total sampling of 34 respondents, 17 intervention respondents at the Palmerah Community Health Center and 17 control respondents in Kebon Jeruk. There was a difference in the average competency of nurses in the intervention group and the control in the post test value (p-value: 0.000). There is an increase in the competency of the intervention group which continues to increase from the 1st measurement to the 3rd measurement to the 5th measurement which is flet/same as in the control group, the increase in competency is not significant in the 2nd measurement to the 5th measurement. Supervision has an effect on increasing the competency of nurses in implementing five moment hand washing patient safety within an optimal period of 3 weeks. It is hoped that the function of supervision the quality    management of community health center nursing will carry out supervision in stages and programmed manner. Keywords: Hand Washing, Nurse Competence, Supervision  ABSTRAK Pendahuluan Keselamatan pasien cuci tangan five moment merupakan tindakan meminimalkan timbulnya risiko pelayanan dalam upayah pencegahan dan pengendalaian infeksi. Tujuan Penelitian ini untuk mengetahui pengaruh supervisi terhadap kompetensi perawat dalam pelaksanaan keselamatan pasien cuci tangan five moment Metode penelitian ini menggunakan Quasi Eksperiment dengan pendekatan pre post test with control group design. Populasi dalam penelitian ini 34 perawat dengan tehnik total sampling, 17 responden intervensi di Puskesmas Palmerah dan kontrol 17 responden di Kebon Jeruk   Hasil penelitian Ada perbedaan rata-rata kompetensi perawat kelompok intervensi dengan kontrol pada nilai post test (p-value: 0,000). Adanya peningkatan kompetensi kelompok intervensi yang terus meningkat dari pengukuran ke1 sampai pengukuran ke 3 sampai pengukuran ke 5 yang flet/sama pada kelompok kontrol peningkatan kompetensi secara tidak signifikan pada pengukuran ke 2 sampai pengukuran ke 5   Kesimpulan supervisi berpengaruh terhadap peningkatan kompetensi perawat dalam pelaksanaan keselamatan pasien cuci tangan five moment  dalam waktu optimal 3 minggu. Diharapkan fungsi pengawasan manajemen mutu keperawatan puskesmas melakukan supervisi secara berjenjang dan terprogram Kata Kunci: Cuci Tangan, Kompetensi Perawat, Supervisi